2019
DOI: 10.1016/j.maturitas.2019.04.211
|View full text |Cite
|
Sign up to set email alerts
|

Electronic assistive technology for community-dwelling solo-living older adults: A systematic review

Abstract: The proportion of older adults who live alone in single households is growing continuously. In the care of these solo-living older adults, electronic assistive technology (EAT) can play an important role. The objective of this review is to investigate the effects of EAT on the wellbeing of community-dwelling older adults living alone in single households. A systematic review of English articles was conducted based on PMC, Scopus, Web of Science and the Cochrane database. Additional studies were identified from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Furthermore, the intervention mapping approach led to a thorough needs assessment that was both informed by end users and the best available current evidence. The iterative continuous testing along development also helped avoiding the replication of common shortcomings of technology targeting older adults, like unfriendly features to their levels of technology literacy [ 11 ]. Early lab tests, for example, helped to pin-point components that needed adaptation (i.e., registration, links in emails) for older adults’ needs before large scale deployment, preventing later difficulties in the implementation and evaluation stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the intervention mapping approach led to a thorough needs assessment that was both informed by end users and the best available current evidence. The iterative continuous testing along development also helped avoiding the replication of common shortcomings of technology targeting older adults, like unfriendly features to their levels of technology literacy [ 11 ]. Early lab tests, for example, helped to pin-point components that needed adaptation (i.e., registration, links in emails) for older adults’ needs before large scale deployment, preventing later difficulties in the implementation and evaluation stages.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it can also create problems, such as decreased sense dignity and stigmatization for the AT user or caregiver, or increased difficulties in performance if the AT does not fit adequately the user or caregiver’s needs which could lead to AT abandonment [ 5 , 6 , 7 ]. Some of these issues can be resolved through post-delivery training and follow-up, leading to better AT use and adoption [ 8 , 9 , 10 , 11 ]. The adoption of AT is behavior-based as it involves learning new behaviors around the use of objects and technology and integrating these learnings in one’s daily living [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that HA was well adopted (highly accepted and usable) by FI and their families or caregivers [ 18 ]. Moreover, after 6 and 9 months of follow-up, the benefits of measures of self-determination behaviors and IADL scale scores [ 9 , 19 ] were higher in equipped FI [ 18 - 20 ]. For instance, with normalized scores, at 9 months, the equipped group did not change its IADL scale score, whereas the control group lost 1 SD.…”
Section: Discussionmentioning
confidence: 99%
“…First, all the studies published so far on AT lack empirical evidence of their efficacy, mostly because of shortcomings related to study design (small sample size, irrelevant or nonstandardized measures, short follow-up duration, no control group, etc) [ 9 , 10 ]. Second, despite the many technological innovations available to assist older adults in their daily life [ 9 ], their silo-based nature (one technology per need) makes them challenging to integrate, as older adults require more services to assist an increasing number of ADLs because of multiple, various, and evolving task needs, particularly in the frailty context [ 11 ]. Indeed, the restricted capability to perform ADL remains extremely patient-dependent (individual and need variability) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This high ratio of elderly people and increase in life expectancy combined with the fact that most of these people are living alone have made it necessary to develop more sophisticated techniques and technologies to monitor them. In this regard, artificial intelligence (AI) [3] plays an important role in healthcare, particularly in assistive care technologies [4] for old people owing to the spurt in the Internet of Things (IoT)-based technological applications. In assistive care technology, activity detection is one of the key tasks to prevent accidents that might occur to elderly people.…”
Section: Introductionmentioning
confidence: 99%